(untitled) (Research, Society and Development, 2022)
Purpose: Systematically review the scientific literature on evidence on the use of ivermectin and nitazoxanide as treatment and prophylaxis for COVID-19. Methodology: This systematic review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). PubMed, Lilacs, and SciELO databases were searched on October 14, 2021, to identify studies that evaluated the use of ivermectin and nitazoxanide for treatment or prophylaxis of confirmed or suspected cases of COVID-19. Results: 105 articles were retrieved, of which 9 were included for the final review, four randomized controlled trials, one nonrandomized clinical trial, one retrospective cohort, one cross-sectional study, one case series, and one case report. Most studies were from Brazil, Egypt, and Mexico, evaluated nitazoxanide, and addressed the disease treatment. Conclusions: There is no sufficiently robust scientific evidence to support treatment and/or prophylaxis with ivermectin and nitazoxanide for COVID-19. Although the results found do not indicate an increased risk of adverse events to the drugs analyzed, it should not be assumed that their use is risk-free and should be used rationally.